Serum Oxidative Stress Biomarkers (MDA, SOD, GSH-Px) and IL-6/TNF-α Ratio as Biochemical Indicators of Disease Progression in Pediatric Cariogenic Pulpitis: Oxidative Stress and IL-6/TNF-α in Pediatric Pulpitis - Wang, Mengxing; Xia, Tian; Wang, Ying (Journal of Medical Biochemistry, 2025)
Background: Cariogenic pulpitis is a common pediatric oral disease in which oxidative stress and inflammatory imbalance are increasingly recognized as important pathogenic mechanisms. Biochemical markers such as malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and the serum IL-6/TNF-α ratio may provide insight into disease severity and progression. Methods: A total of 64 children with cariogenic pulpitis admitted between May 2023 and October 2024 were included, along with 64 healthy children as controls. Serum MDA, SOD, GSH-Px, and IL-6/TNF-α ratio were measured using standard biochemical assays (TBA colorimetry, xanthine oxidase method, NADPH-coupled assay, and ELISA). Group comparisons were performed, and correlations with disease stage and caries depth were analyzed using Pearson correlation coefficients. Results: Compared with controls, children with pulpitis had significantly higher MDA and IL-6/TNF-α levels (t = 18.542 and 20.639, both P < 0.001) and lower SOD and GSH-Px activities (t = 8.279 and 12.449, both P < 0.001). Within the pulpitis group (30 early stage, 24 middle stage, 10 late stage), MDA levels were positively correlated with both caries depth and disease severity (r = 0.82, P < 0.05), while SOD (r = –0.78, P < 0.05) and GSH-Px (r = –0.75, P < 0.05) were negatively correlated. The IL-6/TNF-α ratio was positively correlated with both stage and depth (r = 0.71, P < 0.05), increasing significantly with lesion depth (r = 0.56, P < 0.05). Conclusion: Elevated MDA and IL-6/TNF-α ratio reflect greater oxidative and inflammatory burden and are associated with advanced stages of pediatric cariogenic pulpitis, whereas higher SOD and GSH-Px activities are associated with earlier disease. These biochemical indices may serve as adjunctive laboratory markers for evaluating disease progression and guiding therapeutic monitoring in pediatric pulpitis.